Immediate manifestation of acoustic trauma in the auditory cortex is layer specific and cell type dependent - Novák, Ondřej; Zelenka, Ondřej; Hromádka, Tomáš; Syka, Josef (Journal of neurophysiology, 2016)
Exposure to loud sounds damages the auditory periphery and induces maladaptive changes in central parts of the auditory system. Diminished peripheral afferentation and altered inhibition influence the processing of sounds in the auditory cortex. It is unclear, however, which types of inhibitory interneurons are affected by acoustic trauma. Here we used single-unit electrophysiological recording and two-photon calcium imaging in anesthetized mice to evaluate the effects of acute acoustic trauma (125 dB SPL, white noise, 5 min) on the response properties of neurons in the core auditory cortex. Electrophysiological measurements suggested the selective impact of acoustic trauma on inhibitory interneurons in the auditory cortex. To further investigate which interneuronal types were affected, we used two-photon calcium imaging to record the activity of neurons in cortical layers 2/3 and 4, specifically focusing on parvalbumin-positive (PV+) and somatostatin-positive (SST+) interneurons. Spontaneous and pure-tone-evoked firing rates of SST+ interneurons increased in layer 4 immediately after acoustic trauma and remained almost unchanged in layer 2/3. Furthermore, PV+ interneurons with high best frequencies increased their evoked-to-spontaneous firing rate ratios only in layer 2/3 and did not change in layer 4. Finally, acoustic trauma unmasked low-frequency excitatory inputs only in layer 2/3. Our results demonstrate layer-specific changes in the activity of auditory cortical inhibitory interneurons within minutes after acoustic trauma.
Keywords: parvalbuminy; Auditory Cortex; Parvalbumins; sluchové evokované potenciály; Interneurons; akční potenciály; somatostatin; interneurony; zvířata; Action Potentials; myši; myši inbrední C57BL; Somatostatin; Mice; sluchové korové centrum; Mice, Inbred C57BL; Evoked Potentials, Auditory; Hearing Loss, Noise-Induced; Animals; nedoslýchavost z hluku